Formation of uric acid in grain produced by rhyzopertha dominica (f.) - G. A. Zakladnoy; A. V. Yaitskikh; D. S. Stepanenko (Пищевые системы, 2022)
The study describes the peculiarities of the development of uric acid produced by lesser grain borers Rhizopertha dominica during their vital activities in the grain mass. Pollution of grain by insects makes it poisonous. The conventional determination of grain pollution by the number of insects in the intergrain space in several cases (for example, after grain separation) gives a false picture of its actual hazard for human nutrition, which is a possibility for introduction of falsified grain products to the market. This leads to provision of the population with low-quality primary products, which, subsequently, reduces the quality of foods produced from such grain. During their vital activities, insects pollute grain with uric acid, which analysis is proposed as an alternative to the conventional method. The present study is devoted to the determination of the quantitative dependence of uric acid formation in wheat grain on the number of Rhizopertha dominica. It is shown that uric acid formation in grain by this pest is conditioned by the character of its nutrition with the development of a large amount of excrements in a form of fine gray dust with the characteristic odor commonly referred to as “floury dust”. It was established experimentally that the main part of uric acid excreted by the pest is concentrated in “floury dust”. Grain without “floury dust” contains the insignificant amount of uric acid; however, it is closely linked with the density of its pollution with imago Rh. dominica. As grain before milling in milling plants is subjected to thorough cleaning, during which “floury dust” is removed along with other contaminants, it is recommended to sift “floury dust” from grain before determination of uric acid in it.